ELEVEN NEW SPECIES OF CYRTANDRA (GESNERIACEAE) FROM SULAWESI, INDONESIA - Kartonegoro, A.; Bone, R. E.; Atkins, H. J. (Edinburgh Journal of Botany, 2018)
Eleven new species of Cyrtandra (Gesneriaceae) from Sulawesi are described and illustrated: C. albiflora Karton. & H.J.Atkins, C. boliohutensis Karton. & H.J.Atkins, C. gambutensis Karton. & H.J.Atkins, C. hekensis Karton. & H.J.Atkins, C. hendrianii Karton. & H.J.Atkins, C. hispidula Karton. & H.J.Atkins, C. kinhoii Karton. & H.J.Atkins, C. multinervis Karton. & R.Bone, C. nitida Karton. & H.J.Atkins, C. rantemarioensis Karton. & R.Bone and C. rubribracteata Karton. & H.J.Atkins. Illustrations, maps and preliminary conservation assessments are provided for all the species.